Validation of a Pre-Existing Scoring System for Preoperative Prediction of Difficulty in Laparoscopic Cholecystectomy - Sidra Riaz, Naveed Ali Khan, Abdul Khalique, Raazia Ramzan, Munira Abdul Aziz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most commonly performed surgeries globally is Laparoscopic Cholecystectomy (LC) which is the gold standard surgical procedure for removal of gallbladder. It provides numerous benefits over open cholecystectomy but has also shown higher complication rates. Therefore, a system devised for pre operative assessment of intra operative difficulty level of Laparoscopic Cholecystectomy should be adopted to help with preparedness for complications and ensure an efficient course of surgery. Objective: The aim of this study was to validate a scoring system made by Randhawa Et al to assess intra operative difficulty level of Laparoscopic Cholecystectomy preoperatively. Study Design: This is a non randomized prospective observational study Methodology: This study was conducted in the department of general surgery unit 2 at Dow University Hospital, Karachi, Pakistan on 202 patients. Age, gender, BMI, history of previous hospitalization, examination finding of palpable gallbladder, previous abdominal surgery scars and sonographic findings including wall thickness of gallbladder, pericholecystic collection and impacted stone were considered to score a patient preoperatively. Results: Male gender and presence of pericholecystic fluid collection were found to be statistically significant in predicting intraoperative difficulty in patients undergoing laparoscopic cholecystectomy. Practical implications: Around 7 to 35% of laparoscopic cholecystectomy ends up getting converted into open cholecystectomy. This could be due to various reasons one of which is due to lack of preparedness for intraoperative difficulty in performing the surgery. For this reason, a scoring system that accurately predicts difficulty of surgery could help reducing this rate. Keeping this benefit in mind, a preformed scoring system was tested for its validity in assessing the intraoperative difficulty level of LC preoperatively. Keywords: Laparoscopic cholecystectomy, Scoring system, complications